Potensi tepung daun sirsak, serai, kenikir, jeruk nipis, dan kluwih terhadap kumbang bubuk kedelai (Callosobruchus analis F.) pada kedelai (Glyxine max L.) dalam simpanan - Laily Dwi Dzulhijja; Wagiyana W; Sigit Prastowo (Department of Plant Protection, Faculty of Agriculture, Universitas Jember - Indonesia, 2020)
This study aims to determine the effect of soursop leaf flour, lemongrass flour, kenikir leaf flour, lime leaf flour, and kluwih leaf flour on: 1) mortality, 2) damage to seeds, 3) shrinkage of seed weight, 4) appearance of adult C. analysts on soybean seeds in deposits and 5) laying eggs of C. analis imago female eggs, 6) probit analysis LT50. The experiment was carried out using a Completely Randomized Design (CRD). As treatments are: A) controls; B) soursop leaf flour in doses of 1 g, 2 g, and 3 g; C) Serai leaf flour with doses of 1 g, 2 g, and 3 g; D) kenikir leaf flour with doses of 1 g, 2 g, and 3 g; E) lime leaf flour with doses of 1 g, 2 g, and 3 g; and F) kluwih leaf flour with doses of 1 g, 2 g, and 3 g. Each treatment uses five replications. The observed parameters were analyzed by